(untitled) (Филологические заметки, 2019)
The “Gofman’s» part of long poem «The Way of All the Earth» is analyzed in the article. The author pays attention on conditional-associative aspect of the long poem: signs, codes, dreams, symbols, doubles, mirror-images etc. Learning about role of the Gofman’s traditions in the long poem, the author demonstrates that paradoxes of midnight «gofmaniana” help to understand the world of ominous century.